Increased risk of herpes zoster in children with cancer: A nationwide population-based cohort study. Issue 30 (July 2016) - Lin, Hsiao-Chuan; Chao, Yu-Hua; Wu, Kang-Hsi; Yen, Ting-Yu; Hsu, Yu-Lung; Hsieh, Tsung-Hsueh; Wei, Hsiu-Mei; Wu, Jhong-Lin; Muo, Chih-Hsin; Hwang, Kao-Pin; Peng, Ching-Tien; Lin, Cheng-Chieh; et al.
Abstract : Abstract: Herpes zoster is rare in healthy children, but immunocompromised persons have an increased risk of herpes zoster and severe diseases. Considering the very limited information on herpes zoster in children with cancer, we performed a nationwide population-based cohort study to estimate the incidence of herpes zoster in children with cancer and to explore the association between the 2 diseases. Data were obtained from the National Health Research Institutes Database in Taiwan. A total of 4432 children with newly diagnosed cancer between 2000 and 2007 were identified as the cancer cohort, and 17, 653 children without cancer frequency-matched by sex and age at entry were considered the noncancer cohort. The association between herpes zoster and childhood cancer was determined. Children with cancer had a higher risk of herpes zoster. The incidence rate of herpes zoster was higher in the cancer cohort than in the noncancer cohort (20.7 vs 2.4 per 10, 000 person-years; IRR = 8.6; 95% CI = 4.8–15.6). The cumulative incidence was significantly higher in the cancer cohort ( P < 0.0001). Leukemia, lymphoma, and solid tumor were all associated with the increased risk, and leukemia had the highest magnitude of strength of association. This nationwide population-based cohort study demonstrated that children with cancer were associated with an increased risk of herpes zoster. In addition to early antiviral treatment, vaccination with heat-treated zoster vaccine or adjuvanted subunit vaccine could be an appropriate policy to decrease the incidence in children with cancer.